Conserved residues are critical for Haloferax volcanii archaeosortase catalytic activity: Implications for convergent evolution of the catalytic mechanisms of non‐homologous sortases from archaea and bacteria. Issue 3 (23rd March 2018) - Abdul Halim, Mohd Farid; Rodriguez, Ronald; Stoltzfus, Jonathan D.; Duggin, Iain G.; Pohlschroder, Mechthild
Summary: Proper protein anchoring is key to the biogenesis of prokaryotic cell surfaces, dynamic, resilient structures that play crucial roles in various cell processes. A novel surface protein anchoring mechanism in Haloferax volcanii depends upon the peptidase archaeosortase A (ArtA) processing C‐termini of substrates containing C‐terminal tripartite structures and anchoring mature substrates to the cell membrane via intercalation of lipid‐modified C‐terminal amino acid residues. While this membrane protein lacks clear homology to soluble sortase transpeptidases of Gram‐positive bacteria, which also process C‐termini of substrates whose C‐terminal tripartite structures resemble those of ArtA substrates, archaeosortases do contain conserved cysteine, arginine and arginine/histidine/asparagine residues, reminiscent of His‐Cys‐Arg residues of sortase catalytic sites. The study presented here shows that ArtA WT ‐GFP expressed in trans complements Δ artA growth and motility phenotypes, while alanine substitution mutants, Cys 173 (C173A), Arg 214 (R214A) or Arg 253 (R253A), and the serine substitution mutant for Cys 173 (C173S), fail to complement these phenotypes. Consistent with sortase active site replacement mutants, ArtA C173A ‐GFP, ArtA C173S ‐GFP and ArtA R214A ‐GFP cannot process substrates, while replacement of the third residue, ArtA R253A ‐GFP retains some processing activity. These findings support the view that similarities between certain aspects of the structures and functions of the sortases and archaeosortases are the result of convergent evolution. Abstract : Although evolutionarily unrelated, bacterial sortases and archaeal archaeosortases both recognize and process the C‐termini of substrates having similar tripartite structures, followed by covalent attachment to the cell surface via the newly generated C‐termini. Here, we show that, similar to the sortase, the archaeosortase active site contains a catalytic triad of amino acids that processes the substrates. However, in archaeosortases, but not sortases, these residues appear to be located within three conserved transmembrane segments.